Computer Methods in Mechanics Lectures of the CMM 2009 - Kuczma, Mieczyslaw; Wilmanski, Krzysztof (Advanced Structured Materials,, 2010)
Prominent scientists present the latest achievements in computational methods and mechanics in this book. These lectures were held at the CMM 2009 conference.